Video requests (original, Jan to March). What to do if ... Professional conduct dilemmas for teachers / producer, Estelle Currie ; Brook Lapping. - Currie, Estelle (SILLVR Alexander Street., 2010)
"This short video features NQTs discussing potential dilemmas for professional conduct. Alan Newland from the GTC introduces NQTs from the University of Hertfordshire to topics which may crop up in their careers. Discussion topics cover: online social media networks, extreme political views, flirtatious banter and life outside school."